Synthetic control on structure/dimensionality and photophysical properties of low dimensional organic lead bromide perovskite - Haris, Muhammed P. U.; Bakthavatsalam, Rangarajan; Shaikh, Samir; Kore, Bhushan P.; Moghe, Dhanashree; Gonnade, Rajesh G.; Sarma, D. D.; Kabra, Dinesh; Kundu, Janardan (Inorganic chemistry, 2018)
Low dimensional lead halide perovskites have attracted huge research interest due to their structural diversity and remarkable photophysical properties. The ability to controllably change dimensionality/structure of perovskites remains highly challenging. Here, we report synthetic control on structure/dimensionality of ethylenediammonium (ED) lead bromide perovskite from a two dimensionally networked (2DN) sheet to a one dimensionally networked (1DN) chain structure. Intercalation of solvent molecules into the perovskite plays a crucial role in directing the final dimensionality/structure. This change in dimensionality reflects strongly in the observed differences in photophysical properties. Upon UV excitation, the 1DN structure emits white light due to easily formed “self-trapped” excitons. 2DN perovskites show band edge blue emission (∼410 nm). Interestingly, Mn2+ incorporated 2DN perovskites show a highly red-shifted Mn2+ emission peak at ∼670 nm. Such a long wavelength Mn2+ emission peak is unprecedented in the perovskite family. This report highlights the synthetic ability to control the dimensionality/structure of perovskite and consequently its photophysical properties.

Ferroelectric aminophosphonium cyanoferrate with a large electrostrictive coefficient as a piezoelectric nanogenerator - Vijayakanth, Thangavel; Sahoo, Supriya; Kothavade, Premkumar; Sharma, Vijay Bhan; Kabra, Dinesh; Zareba, Jan K. K.; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (Angewandte Chemie-International Edition, 2023)
Hybrid materials possessing piezo- and ferroelectric properties emerge as excellent alternatives to conventional piezoceramics due to their merits of facile synthesis, lightweight nature, ease of fabrication and mechanical flexibility. Inspired by the structural stability of aminophosphonium compounds, here we report the first A(3)BX(6) type cyanometallate [Ph-2((PrNH)-Pr-i)(2)P](3)[Fe(CN)(6)] (1), which shows a ferroelectric saturation polarization (P-s) of 3.71 mu C cm(-2). Compound 1 exhibits a high electrostrictive coefficient (Q(33)) of 0.73 m(4) C-2, far exceeding those of piezoceramics (0.034-0.096 m(4) C-2). Piezoresponse force microscopy (PFM) analysis demonstrates the polarization switching and domain structure of 1 further confirming its ferroelectric nature. Furthermore, thermoplastic polyurethane (TPU) polymer composite films of 1 were prepared and employed as piezoelectric nanogenerators. Notably, the 15 wt % 1-TPU device gave a maximum output voltage of 13.57 V and a power density of 6.03 mu W cm(-2).
Keywords: Cyanometallates; energy conversion; H-bonding; hybrid composites; Phosphorus

Highly electrostrictive salt cocrystal and the piezoelectric nanogenerator application of its 3D-printed polymer composite - Sahoo, Supriya; Panday, Rishukumar; Kothavade, Premkumar; Sharma, Vijay Bhan; Sowmiyanarayanan, Anirudh; Praveenkumar, Balu; Zareba, Jan K.; Kabra, Dinesh; Shanmuganathan, Kadhiravan; Boomishankar, Ramamoorthy (ACS Applied Materials and Interfaces, 2024)
Ionic cocrystals with hydrogen bonding can form exciting materials with enhanced optical and electronic properties. We present a highly moisture-stable ammonium salt cocrystal [CH3C6H4CH(CH3)NH2][CH3C6H4CH(CH3)NH3][PF6] ((p-TEA)(p-TEAH)PF6) crystallizing in the polar monoclinic C2 space group. The asymmetry in (p-TEA)(p-TEAH)PF6 was induced by its chiral substituents, while the polar order and structural stability were achieved by using the octahedral PF6- anion and the consequent formation of salt cocrystal. The ferroelectric properties of (p-TEA)(p-TEAH)PF6 were confirmed through P-E loop measurements. Piezoresponse force microscopy (PFM) enabled the visualization of its domain structure with characteristic ``butterfly'' and hysteresis loops associated with ferro- and piezoelectric properties. Notably, (p-TEA)(p-TEAH)PF6 exhibits a large electrostrictive coefficient (Q(33)) value of 2.02 m(4) C-2, higher than those found for ceramic-based materials and comparable to that of polyvinylidene difluoride. Furthermore, the composite films of (p-TEA)(p-TEAH)PF6 with polycaprolactone (PCL) polymer and its gyroid-shaped 3D-printed composite scaled-up device, 3DP-Gy, were prepared and evaluated for piezoelectric energy-harvesting functionality. A high output voltage of 22.8 V and a power density of 118.5 mu W cm(-3) have been recorded for the 3DP-Gy device. Remarkably, no loss in voltage outputs was observed for the (p-TEA)(p-TEAH)PF6 devices even after exposure to 99% relative humidity, showcasing their utility under extremely humid conditions.
Keywords: 3D printing; cocrystals; energy harvesting; ferroelectricity; Piezoelectricity